NALISIS PENGARUH LINGKUNGAN KERJA, MOTIVASI DAN KOMPENSASI TERHADAP KEPUASAN KERJA PEGAWAI PADA LEMBAGA PEMBINAAN KHUSUS ANAK KLAS II PEKANBARU - -, Dian Norita Margaretha - (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2023)
This study aims to examine the effect of the work environment, motivation and compensation on employee job satisfaction at the Special Development Institute for Class II Children Pekanbaru. This research was conducted at Correctional Street Number 004, Rumbai District, Pekanbaru City 28264. The type of data used in this research is quantitative data. with data sources used primary and secondary. Primary data is data collected through questionnaires and interviews as instruments to prove research results, and secondary data is results obtained from books, journals and the internet. The population in this study amounted to 59 people, and the sampling technique in this study was saturated sampling or census. To test the hypothesis in this study, namely using the instrument test, classical assumption test, hypothesis testing and multiple linear regression testing using the SPSS version 25.0 application. The results of this study indicate that the work environment has a significant effect on the job satisfaction of employees of the Pekanbaru Class II Special Children Development Institute, motivation has a significant effect on the job satisfaction of the Pekanbaru Class II Special Children Development Institute employees, compensation has a significant effect on employee satisfaction of the Pekanbaru Class II Special Children Development Institute and from the results of the research conducted, simultaneous multiple linear regression tests show that the variables l work environment, motivation and compensation have a significant effect on employee job satisfaction at the Special Development Institute for Class II Children Pekanbaru. Keywords: Work Environment, Motivation, Compensation, Job Satisfaction.